2020
DOI: 10.1177/0741932520918859
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Ethics of Punishment-Based Procedures for Young Children With Disabilities

Abstract: Punishment-based procedures are used to reduce challenging behavior in both special education and applied behavior analytic practices. Although commonly effective, these interventions are associated with an increased level of risk, making their use controversial. However, no research has specifically analyzed the extent to which researchers comply with the ethical standards of the professional organizations for special educators and behavior analysts (i.e., Council for Exceptional Children [CEC] and the Behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…According to Pokorski and Barton (2020), behavior-analytic research must be conducted in accordance with ethical standards by evaluating reinforcement-based procedures prior to implementing punishment-based procedures (BACB, 2020). Col on et al ( 2012) did this by directly targeting appropriate vocalizations with verbal operant training before redirecting stereotypy with RIRD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Pokorski and Barton (2020), behavior-analytic research must be conducted in accordance with ethical standards by evaluating reinforcement-based procedures prior to implementing punishment-based procedures (BACB, 2020). Col on et al ( 2012) did this by directly targeting appropriate vocalizations with verbal operant training before redirecting stereotypy with RIRD.…”
Section: Discussionmentioning
confidence: 99%
“…C-RD paired with a DRA might be effective in cases that RIRD is ineffective, but further evaluations are necessary to systematically compare RIRD and C-RD to quantify the procedure corresponding to higher levels of contextually appropriate behavior and less time redirecting stereotypy. Given the recommendations of Pokorski and Barton (2020), RIRD and C-RD should be compared while reinforcement is simultaneously available for appropriate behavior. Additionally, future investigations involving C-RD should recruit parent or teacher feedback on the acceptability of procedures and the degree to which the results are socially meaningful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical principles such as authority, human dignity, privacy, and confidentiality can easily be compromised in pediatric settings [ 16 – 18 ]. The systematic review of the literature conducted by Pokorski and Barton in 2020 revealed that although the code of ethics is established to guide nurses in research and practice, they are not adhered to by researchers in the field of pediatric nursing [ 19 ]. In the study of Beykmirza and colleagues (2019), it was reported that Nurses reported significantly higher levels of ethics than mothers of children with cancer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, because interventions based on reinforcement alone are not universally effective, behavior analysts may forgo these interventions and implement punishment‐based strategies immediately, either alone or in combination with reinforcement. In a recent review of the ethical use of punishment‐based interventions for preschool children, seven studies implemented punishment (either response interruption and redirection [RIRD] or overcorrection) contingent on stereotypy; only three of these seven studies documented that reinforcement‐based strategies were attempted and were ineffective prior to the use of punishment (Code Variable 13; Pokorski & Barton, 2020). Although it is unknown whether this is due to a lack of reporting or other factors, it is essential that punishment‐based procedures are not implemented when they are unwarranted.…”
mentioning
confidence: 99%